URGENSITAS ASPEK KEPRIBADIAN BAGI GURU PAI - Hilyah Ashoumi (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2018)
Education is an important factor in improving the quality of human life, especially improving the quality of learners to have a broad knowledge, noble character, and beneficial to life in society. This educator is teacher as the central figure of education, must be exemplary his morality beside that his scientific and academic skills. In addition, the teacher have to the responsibility, religion to educate the students to be the knowledgeable, and morals. Educators are as professionals that charge of planning and implementing the learning process, he is the person who seeks to guide, improve, perfect, and purify the students so that the heart becomes close to khaliqnya